Biodiesel Production from Kapok Seed Oil (Ceiba pentandra) Through the Transesterification Process by Using CaO as Catalyst (Global Journals of Research in Engineering, 2012)
The purpose of this research is to make biodiesel from Kapok Randu ( name of kapok in Indonesia ) seed oil (Ceiba pentandra), studied the effect of operating variables on the performance of the catalyst (CaO) in Kapok Randu oil transesterification process and knows the regeneration ability of the catalyst (CaO). In this research the variables used are the oil to methanol mole ratio 1:10, 1:15, and 1:20, the temperature of reaction is 40 #xBA; C, 50 #xBA; C and 60 #xBA; C and the transesterification reaction time is 1 hour, 2 hours and 3 hours with CaO catalyst used is 7% of the mass of kapok oil. From the research, the highest yield obtained in the variable mole ratio of 1:15 methanol, the reaction temperature of 60#x2DA; C and the transesterification reaction for 1 hour is 88.576%. In addition, CaO catalyst can be regenerated up to 3 times with the smallest yield obtained that is 64.3%.
Keywords: Biodiesel; kapok seed oil; Ceiba pentandra; calcium oxide